Nanocrystal light-emitting diodes based on type II nanoplatelets - Liu, Baiquan (2020)
Colloidal semiconductor nanoplatelets (NPLs) have recently emerged as a new family of semiconductor nanocrystals with distinctive structural and electronic properties originating from their atomically flat architecture. To date, type II NPLs have been demonstrated to possess great potential to optoelectronic applications, such as solar cells and lasers. Herein, nanocrystal light-emitting diodes (LEDs) based on type II NPLs have been developed. The photoluminescence quantum yield of these used type II NPL (CdSe/CdSe0.8Te0.2 core/crown) is close to 85%. By exploring an effective inverted structure with the dual hole transport layer, the NPL-LEDs exhibit i) a turn-on voltage of 1.9 V, ii) a maximum luminance of 34520 cd m−2, iii) an EQE of 3.57% and a PE of 9.44 lm W−1. Compared with previous NPL-based LEDs, the performance of our devices is remarkably enhanced. For example, the luminance is 350-fold higher than the best inverted NPL-based LED. The findings may not only represent a significant step for NPL-based LEDs, but also unlock a new opportunity that this class of type II NPLs materials are promising for developing high-performance LEDs.